Socialization of Environmental Awareness through Identification of Waste Problems in Sungai Ancar, Kekalik Jaya Village, Mataram City: Sosialisasi Kesadaran Lingkungan melalui Identifikasi Permasalahan Sampah di Sungai Ancar, Kelurahan Kekalik Jaya, Kota Mataram - Astia Ramadani; Auralia Salsadila; Baiq Halimatusakdiah; Baiq Hanira Septiana; Dwi Riski Aulia (Yayasan Siti Widhatul Faeha, 2026)
Environmental awareness socialization through the identification of waste problems in rivers is an important approach in community-based environmental education. Sungai Ancar in Kekalik Jaya Village, Sekarbela District, Mataram City, is one of the urban rivers facing serious waste pollution problems due to residents' behavior of disposing of household waste directly into the river. This community service activity aimed to identify the types and distribution of waste, understand residents' behavior regarding waste disposal, and provide environmental awareness education to housewives living along the riverbank. The activity was conducted in June 2026 using a qualitative descriptive approach through participatory observation and unstructured interviews carried out simultaneously at the river site. Field observations identified three main categories of waste: inorganic waste (plastic bags, bottles, and styrofoam), organic waste (leaves, bamboo twigs, and food scraps), and household hazardous waste (used sanitary pads and diapers). Waste was found floating on the water surface, accumulated along the riverbank, and clogging the bridge structure. The urgency of this issue was reinforced by the major flood on July 6, 2025, which impacted 30,681 residents of Kekalik Jaya. Post-activity evaluation indicated a shift in residents' perception, particularly in recognizing the link between waste disposal habits and flood risk. This activity demonstrates that participatory in-situ socialization is effective in building environmental awareness; however, it must be supported by systemic policy improvements in waste management infrastructure.